Estimation of rock core indices for development of underground infrastructure using non-invasive geophysical methods - Hasan, Muhammad; Shang, Yanjun; Qi, Shengwen; Meng, Qingsen (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2024)
Rock mass characterization offers the basis of the stability criterion for the planning and advancement of civil engineering projects. Rock core index (RCI) is one of the key geotechnical parameters adopted in rock mechanics and rock engineering. RCI provides risk assessment regarding the success criteria of engineering design. Consequently, an accurate estimate of such parameters is a challenging task in the context of credibility, budget, and time. However, the traditional estimation of geomechanical parameters needs lots of drilling tests at some selected points. The point-scale data often cause more ambiguity and less authenticity in engineering design. Besides, the conventional approaches are invasive, uneconomical, and laborious and cannot investigate the complete project site. We offer an indirect technique for the estimate of RCI using empirical relationships between drilling and geophysical data, which addresses the drawbacks of the conventional methods. Geophysical techniques offer the subsurface volumetric data and are faster, more affordable, and easier to use. In this study, we employ a non-invasive CSAMT (controlled-source audio-frequency magnetotellurics) method for the first time to quickly assess 2D and 3D RCI models. The suggested approach assesses the intricate geological subsurface at a depth of 1 km in order to produce a more precise and complete image of the quality of the rock mass across a wide area. These findings are crucial for improving our understanding of the intricate geological conditions, estimating the likelihood of failure early on, and supporting the safe, stable, and cost-effective construction of deep underground engineering structures. In regions where there is a deficiency of mechanical drilling data, our approach decreases the gaps between an appropriate geotechnical model and insufficient data, yields more objective indices, and serves as a guide for more correct engineering structure design.